Renewable knowledge in socio-technical systems: a service science perspective on public information infrastructures - Crihană, Ioana; Sgârciu, Valentin; Rebenda, Josef (ICI Publishing House, 2025)
Amid the accelerating digital transition, the knowledge systems face growing risks of fragmentation and epistemic discontinuity. To address these challenges, the public libraries are increasingly recognized as strategic socio-technical infrastructures that sustain the recovery, renewal, and long-term preservation of knowledge. Building on the view of knowledge as a renewable resource - one that can be created, reinterpreted, and recombined across social contexts - this paper introduces the concept of renewable knowledge, defined as the dynamic property of knowledge to be continuously updated, co-created, and adapted through human-service-technology interaction for public value creation. Anchored in the Service Science and Knowledge Commons theory, the study examines how public libraries operate as aggregators of renewable knowledge through the open data mediation, big data valorisation, and AI-assisted information services. Employing a mixed-methods design (survey and structured interviews across Romanian and European public libraries), the empirical results identify six conceptual clusters reflecting how libraries enact renewable knowledge via creation, utilization, organization, and distribution. Findings demonstrate that libraries move beyond static information management toward participatory knowledge stewardship, fostering resilience, sustainability, and collective intelligence within socio-technical ecosystems.
Keywords: Service Science; Renewable Knowledge; Service Ecosystem; Knowledge Assets; Knowledge Stewardship